Diagnosis of soil contamination using microbiological indices: A review on heavy metal pollution. (15th July 2019) - Tang, Jiayi; Zhang, Jiachao; Ren, Liheng; Zhou, Yaoyu; Gao, Jun; Luo, Lin; Yang, Yuan; Peng, Qinghui; Huang, Hongli; Chen, Anwei
Abstract: Heavy metal contamination of soil has become a serious global issue because of their persistence in the environment and the non-biodegradable nature leading to their accumulation to toxic levels. In order to achieve early warning and prevent soil quality from deteriorating, it is necessary to select suitable indices to diagnose heavy metal pollution. Microbiological indices for monitoring soil pollution by heavy metals are gaining attention. However, the related researches are scattered, and critical review is imperative. This review is mainly to provide readers with an in-depth understanding of the merits and limitations of microbiological indices for heavy metals contaminated and remediated soils. Microbiological indicators include microbial abundance, community diversity and structure, functional activity. The changes of different microbiological indices and the mechanism of microbial response to heavy metal stress in soils are comprehensively summarized. Furthermore, research gaps and future directions of the microbial ecotoxicological diagnosis of soil contamination by heavy metals are also proposed and discussed. Highlights: Diagnosis using microbiological indices in soils with HM reviewed. Merits and limitations of indices were discussed. Soil quality should be diagnosed with a complete set of biological indicators. Discussing quantitative relationship between soil physicochemical factors and microbial indicators is needed. A large-scale in-situ investigation is needed.